Early Adolescents' Risk Taking Propensity, Urban Stress, and Affiliation With Risky Peers. (May 2021) - Dykas, Matthew J.; Goplen, Joanna; Ewart, Craig K.; Gump, Brooks B.
This study examined how early adolescents' risk taking propensity and urban stress were linked to their affiliation with risky peers. Participants ( n = 297;X ¯ age = 10.48 years [ SD = 0.93 years]; 54% male; 58% Black/African American) completed a brief laboratory-based behavioral risk taking task. They also completed self-report measures of urban stress and the number of close friends engaged in various risky behaviors (e.g., smoking, stealing). Results supported a link between risk taking propensity and affiliation with risky peers that was moderated by urban stress. After controlling for demographic factors, early adolescents' risk taking propensity was positively associated with affiliation with risky peers at high levels of urban stress but not at low levels of urban stress.